Analisis Pengaruh Faktor-Faktor Rasio Keuangan Terhadap Profitabilitas - Hasibuan, Henny Triyana (E-Jurnal Akuntansi; Vol 34 No 2 (2024)DO - 10.24843/EJA.2024.v34.i02.p07, 2024)
The purpose of this study is to identify the factors that affect the profitability of Islamic commercial banks in Indonesia. The population of this study is Islamic commercial banks in Indonesia which are listed on the IDX for the period 2018-2021. The sampling technique used was purposive sampling. The number of samples used is 10 Islamic commercial banks with an observation period of 4 years, the total research sample is 40 observations. The independent variables in this study are NPF, FDR, BOP, CAR and NOM, while the dependent variableis profitability which is proxiesin ROA. The data analysis technique used is multiple linear regression. The results showed that the NPF and BOPO variables had a negative effect on profitability, while the FDR, CAR andNOM variables had apositive effect. The results of this study support the signal theory, all variables provide a signal on the profitability of Islamic Commercial Banks in Indonesia. Keywords:NPF;FDR;BOPO;CAR;NOM;Profitability.